TESTING OF THE SOLAR THERMAL COOKING PERFORMA OF THE ENERGY CONVERSION TECHNOLOGY CENTER AGENCY OF TECHNOLOGY ASSESSMENT AND APPLICATION - Adam Prasetyo Nugroho; Rivai Mustafa; Mujahid Wahyu (VANOS Journal of Mechanical Engineering Education, 2019)
Performance testing of solar thermal cooking. At the large institute of energy conversion technology, the body's assessment and application of technology. Practical Work. Serang: Mechanical Engineering Education, Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University, 2019. Solar thermal cooking is a technology that works by utilizing solar energy. This test uses observational methods, interviews, documentation and experiments, to determine the performance of solar cooking that is being developed by the Center for Energy Conversion Technology as a cooking aid to reduce or can replace firewood, LPG gas and electric stoves. The purpose of testing is the use of alternative energy that can be developed and possibly can be produced as a renewable technology. Conclusions testing for solar thermal cooking performance obtained data such as the highest radiation 930,211 W / m ^ 3 for the temperature 166⁰C these data as a result of the performance of solar cooking performance and the results of the temperature test produced on cooking reached> 80⁰C the temperature can pass the cooking conditions starting from boiling water, boiling eggs and so on.